Pushing down infinite Loeb measures - Ross, David A. (MATHEMATICA SCANDINAVICA, 2009)
Sufficient conditions are given under which the standard part map on an arbitrary Hausdorff space can be used to push down an infinite nonstandard measure. This makes it easier to construct standard infinite Borel measures using nonstandard techniques.